Manajemen Evaluasi Pesantren: Dulu, Kini dan Nanti - Ujang Miftahudin; Jaelani Husni (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2024)
Islamic boarding school evaluation management in historical perspective is an interesting topic to research considering that Islamic boarding schools as typical traditional Islamic educational institutions in Indonesia must adapt to the massive challenges of the times due to the rapid flow of technology and information. This research was conducted to see the history of Islamic boarding schools in Indonesia, and to see how Islamic boarding schools should respond to the challenges of the times. This research was carried out by means of a literature study, using historical research methods, including heuristics, criticism, interpretation and historiography. Islamic boarding school evaluation management has historically been marked by the spread and development of Islam in the archipelago, one of which is the existence of the Quro Islamic Boarding School in Karawang Regency. The challenge that must be faced is to review the Islamic Boarding School Law and be able to utilize this policy both for Islamic boarding school institutions and for the economic independence of the community.